Indicadores edáficos e bióticos de restauração em área de Mata Atlântica no Estado de Sergipe - Nery, Fernanda Cristina Aguiar Mendonça (2023)
This study addresses forest restoration in an area of the Atlantic Forest, a globally important ecosystem that is highly fragmented and exploited in Brazil. This paper focuses on the evaluation and monitoring phase of the restoration process, which is essential for understanding the progress achieved. The objective of the study is to present biotic and edaphic indicators of an area 17 years after implementation of forest restoration and to establish reference values for these indicators. The aim of this approach is to respond to challenges such as obtaining simple and effective indicators and dealing with the lack of reference values for evaluation and the difficulty of long-term and large-scale monitoring. Three distinct areas were analyzed in this study: a forest restoration area owned by Votorantim Cimentos - S.A. (CIMESA) in the municipality of Laranjeiras, SE; a reference ecosystem, FLONA do Ibura; and an agricultural area growing sugarcane. The goal was to evaluate edaphic properties over the years of restoration, considering different positions in the landscape and land uses. At 17 years after implementation of restoration efforts, soil fertility has not yet reached levels similar to those found in the reference ecosystem; topography has proven to be an important factor affecting soil chemical properties. Additionally, the biotic properties of the vegetation were evaluated using in situ analysis and geoprocessing tools. Phytosociological analyses were carried out, and determinations were made of the diversity and equity indices of species, carbon and biomass accumulation, Gross Primary Productivity (GPP), Net Primary Productivity (NPP), Dry Biomass, and the Normalized Difference Vegetation Index (NDVI). The area is in a full restoration process, with dense vegetation cover and a closed canopy, albeit with low species diversity and equitability. The restored area has recovered several ecosystem services, such as soil protection, biomass accumulation, and carbon storage. The results obtained contribute to forest restoration studies, establishing reference values for the regional ecosystem and assisting decision making for current and future projects.